The effect of self-awareness on the ability to recognize personal motion - Bories, T. L.; Hyllegard, R.; Maharjan, P.; Brown, J. A. (Journal of Human Sport & Exercise, 2022)
The purpose of this study was to examine the abilities of athletes with specific gait training (i.e., runners) discriminating personal gait from point-light videos were compared to athletes for whom gait is not a trained aspect of the sport (i.e., swimmers), and that of a control. It was hypothesized that runners would discriminate their gait among different individuals with greater accuracy than the other two groups and that runners would also devote more attention to the lower extremities for recognition indications. Results showed that runners group recognized themselves more often than the other two groups (p = .048, n2 = 0.18), and that runners allotted more visual attention to the lower extremities (p < .05, np 2 = 0.16) when viewing the point-light videos than the other groups. The findings were consistent with other investigations with point-light video representations of movement and suggest that experience and training lead to movement self-awareness that is both recognizable and accessible by a performer.